RCMAS Climate+: Enhanced farm advisory for better decision-making under dynamic weather conditions - Rowena Castillo; Mary Anne R. Gutierrez; Jeny Raviz; Jane Girly Balanza; Maria Angela Barua; Airen Claire Baradas; Cornelia Garcia; Jon Hellin; Alice Laborte (2023)
The Rice Crop Manager Advisory Service (RCMAS) Climate+ generates climate-adjusted nutrient and crop recommendations to address dynamic weather conditions and potential climate-related risks during the cropping season. It is a link between the RCMAS platform, https://rcm.da.gov.ph/ and the Agro-climatic Advisory Portal (ACAP), https://amia-cis.github.io via applications programming interface (API). The RCMAS uses the 6-month seasonal and 10-day weather forecasts from the ACAP to formulate agro-advisories aiming reduce crop loss due to climate risks such as floods and drought. RCMAS Climate+ upgrades the existing RCMAS platform with pre-season and mid-season climate-related recommendations, such as adjustments to date of sowing, fertilizer application timing in response to floods or droughts during the crop growth period and (2) real-time or near-real-time climate information dissemination to farmers, which could enable better decision-making under dynamic climate conditions. The agro-advisories are provided to farmers through the one page printout and/or SMS.